Effect of Bombay Locust (Patanga succincta) and Tapioca Flour or Carrageenan Addition on Quality of Ground Pork Patty - Puechkamutr, Yuporn; Arsa, Supeeraya (My University, 2025)
The quality of ground pork (GP) patty containing ground Bombay locust meal (BM) was investigated. GP was mixed with BM (0–20%) and tapioca flour (0–3%) or carrageenan (0–2%). Patties with 20% added BM had higher protein content (21%), lower cooking loss (23%) and hardness (74693 N) than the GP patty, with no BM as the control. The pH of the patties significantly increased with added BM. The patty cooking loss decreased with added carrageenan or tapioca flour (p < 0.05). The addition of carrageenan increased patty hardness (p < 0.05). The best quality patties were prepared with the addition of 20%BM and 1%carrageenan.
Keywords: Bombay locust; carrageenan; insect; patties; tapioca flour